HARMONIZING THE CONCEPT OF OMNIBUS LAW AS A REGULATORY SOLUTION FOR EDUCATION TRANSFORMATION - Yapiter Marpi (Institut Agama Islam Negeri (IAIN) Bone, 2023)
The quality of human resources is one of the factors that hinder the improvement of the competitiveness of education. Regulatory issues are related to several fields of education that often transform rules that do not improve intellectual quality in the midst of a pandemic. Based on changes in President Joko Widodo's administration, the Working Cabinet separated the Ministry of Education and Culture from the Higher Education Education and merged under the Ministry of Research and Technology under Minister Nadiem Makarim. Therefore the higher education cycle in tertiary institutions is now under the auspices of the Ministry of Education and Culture. Often it may have implementation problems and conflicts between agencies and law enforcement starting with the quality of the applicable regulations. As a result, the regulations and rules of the authorities do not accommodate an increase in the climate of competitiveness of domestic education, but this article conveys a message that the government needs to work out a solution to improve laws through the Omnibus Law. The existence of Omnibus Law is well known in legal theories that are studied in the introduction of legal science in the flow of existing legal systems. The Omnibus Law theory originates from a country that adheres to a common law system even though the Indonesian state itself adheres to a civil law system. For this reason, the purpose of this paper is to understand the Omnibus Law and its use to fix regulatory problems in Indonesia.